Effect of Pomegranate extract punicalagin as a chemopreventive modality on experimentally induced hamster buccal pouch carcinogenesis - Mohamed Alaa Al-Dosoki,; Emad Soliman Al-qalshy,; Ahmed Abd-Alshakor Abd-Alhafez,; Ashraf Yehia Shamia,; Amr Mahmoud Mohamed,; Ashraf Mohamad Emran,; Ahmed Mostafa Abbas,; Ehab Hamed Mostafa Elwardany,; Ahmed Hussein Gaber,; Galal Abou Elyazied Nasr, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: The current study sought to assess the impact ofpunicalagin (PU)as a chemo-preventive method in artificially generated hamster buccal pouch (HBP) carcinogenesis. Material and methods: 40 five-week-old Syrian male hamsters weighing between 80 and 120 grams apiece were split up into four groups of 10 hamsters in every group. Group I involved applying liquid paraffin topically three times per week during 14 weeks, whereas Group II involved applying 7, 12-dimethylbenz[a]anthracene (DMBA) topically 3 times a week for 14 weeks at a concentration of 0.5% in liquid paraffin, Group III: Local placement of DMBA (0.5% in liquid paraffin, three times per week during 14 weeks) + Oral administration of punicalagin (18.5 mg/kg bw by oral ingestion, three times a week for 14 weeks), Group IV: Oral administration of PU alone (18.5 mg/kg bw by oral ingestion, three times per week during 14 weeks on alternate days of DMBA application). Results: The results of gross observation and histological analysis showed that: a) the standard stratified squamous epithelium was present in Group I; b) the SCC was well and moderately differentiated; c) the tumor occurrence was significantly reversed in Group III; and d) the tumor occurrence was normal and comparable to Group I.According to immunohistochemical data, oral PU treatment to hamsters administered with DMBA recovered the normal expression of Bcl-2, Bax, and PCNA, suggesting that PU might possess a chemo-preventive process through pro-apoptotic actions and/or anti-proliferative activity. Conclusion: PU could work across a variety of ways, including selectively causing apoptosis in cancer cells, anti-inflammatory and antioxidant actions, and inhibition of cell migration and proliferation.